Comparative Study of Mulching Practices and Biofertilizers on Yield Attributes of Finger Millet (Variety- VL Mandua 379) - Karge Basar; Kasinam Doruk; K. Subhash Chandra Bose; Lipi Rina; Nabam Akli; Sanchung Lida; Anki Mibang; Karthikeyan M (Archives of Current Research International, 2024)
A field experiment was conducted at Himalayan University farm, Jullang, Itanagar, Arunachal Pradesh, during the kharif season of 2023 with 8 treatments replicated thrice in randomized block design, to determine the effect of different types of mulching and biofertilizer on yield of finger millet (Eleusine coracana.). The available nutrient status showed high nitrogen (N), low phosphorus (P), and medium potassium (K) levels. The experiment included the following treatments T1-Control, T2- Karanj leaf mould at + Azotobacter, T3-Karanj leaf mould + PSB, T4- Neem leaf mould + Azotobacter, T5-Paddy straw + jute bag + Rhizobium, T6-Paddy straw + PSB, T7-Black polythene + Azotobacter and T8-Saw dust + Rhizobium. The highest finger length (cm) recorded was 5.92 cm at harvest, highest test weight (g) recorded was 3.06 g at harvest, highest grain yield (t ha-1) recorded was 4.05 t ha-1 at harvest, highest straw yield (t ha-1) recorded was 7.92 t ha-1 at harvest and harvest index (%) of 34.66 % at harvest were observed with treatment T5 - Paddy straw + jute bag + Rhizobium.